Green building concept for children activity centre; incentive for key players / Siti Zubaidah Hashim and Norida Maziantie Muhammad - Hashim, Siti Zubaidah; Muhammad, Norida Maziantie (2012)
Barriers to certification included problems with the documentation process, a lack of education, and costs associated with government. To implement the Green Building Concept, government and private should combine together to give an incentive to the key players who use the GB Concept in their development. All the building should registered with the council to look the rating for their building. Pertubuhan Arkitek Malaysia(PAM) whose introduce the concept of the green building in the construction industry. They have many criteria to give the rating for any building such as in Leadership in Energy and Environmental Design (LEED) Rating System. For example, an integrated design process, environmental impacts, water conservation, energy efficiency and etc. Based on the criteria, how it can be apply in the Children Activity Centre. This concept can give more comfortable to children during the learning process. This concept also can give advantages to environment and community because it can save on the cost of maintenance and also it can provide a private space to the children. The tool used to achieve best practice in this research is benchmarking for efficiency.